SOCIAL WORKING PENALTY AS SOLUTION IN ERADICATING CORRUPTION IN INDONESIA - Desy Maryani (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption in Indonesia had caused big destruction for existence of a state. Not only cause state finance detriment but also corruption has taken social and economical right of people in common. This kind of crime is very difficult to be eradicated because sometimes it is done systematically and involve authorized people. We can feel how big and extraordinary of corruption impact. It is worthy if corruption is categorized as extraordinary crime that must be eradicated extraordinarily in which one of those is by social working. Problem identification of this problem are 1) how is social working model for corruptor? and 2) how social work penalty as a way in eradicating corruption in Indonesia? Method of approach used in this research is juridical normative approach with secondary data as its source. Based on analysis, it can be concluded that it is necessary to implement heavy punishment for corruptor by social working because it can create a deterrence effect. Social working penalty also can be a solution is corruption eradication in Indonesia. Social working penalty is do a good deed to people and create social working. Key words : social working penalty, eradication, corruption